2012
DOI: 10.3892/mco.2012.24
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of fermented noni exudates and its fractions

Abstract: Abstract. Noni has been extensively used in folk medicine by Polynesians for over 2000 year. Recent studies have shown that noni has a wide spectrum of therapeutic activities including inhibition of angiogenesis, anti-inflammatory effects and anticancer activities. Intraperitoneal (i.p.) injection of fermented noni exudates (fNE) were previously found to induce significant tumor rejection in a S180 mouse sarcoma tumor model, while natural killer (NK) cells were demonstrated to be markedly involved in fNE-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“… Botanical Test sample/compound Animal model Delivery route/dose/duration Outcome Reference Açaí freeze-dried açaí powder 19-month old Fischer rats (n = 15–20/group) oral, ad libitum (2% of diet for 6–7 weeks) increased production of antioxidant marker Nrf2 in hippocampus and frontal cortex improved working memory and behavior 32 , 33 Noni fermented fruit exudates and fractions S180 sarcoma tumor-challenged C57BL/6J mice (n = 4–8/group) oral, ad libitum (0.2 mL i.p. or 5% of drinking water 3d-4 weeks) inhibition of tumor development and suppression of existing tumor cells 44 Tahitian Noni ® juice MMTV-neu transgenic mice (n = 30–45/group) oral, ad libitum (10% v/v drinking water, maximum 14 months) reduction of mammary tumor growth but not incidence 45 pure Costa Rican noni juice carrageenan-induced acute paw edema rat model (n = 8/group) by gavage (14.8 and 37 mg/kg, one time) or i.p. (7.4 and 37 mg/kg, one time) reduction of acute and chronic inflammation 46 asthmatic rat model (ovalbumin-induced, n = 8/group) oral (4.6 mL/kg) and i.p.…”
Section: Açaímentioning
confidence: 99%
See 1 more Smart Citation
“… Botanical Test sample/compound Animal model Delivery route/dose/duration Outcome Reference Açaí freeze-dried açaí powder 19-month old Fischer rats (n = 15–20/group) oral, ad libitum (2% of diet for 6–7 weeks) increased production of antioxidant marker Nrf2 in hippocampus and frontal cortex improved working memory and behavior 32 , 33 Noni fermented fruit exudates and fractions S180 sarcoma tumor-challenged C57BL/6J mice (n = 4–8/group) oral, ad libitum (0.2 mL i.p. or 5% of drinking water 3d-4 weeks) inhibition of tumor development and suppression of existing tumor cells 44 Tahitian Noni ® juice MMTV-neu transgenic mice (n = 30–45/group) oral, ad libitum (10% v/v drinking water, maximum 14 months) reduction of mammary tumor growth but not incidence 45 pure Costa Rican noni juice carrageenan-induced acute paw edema rat model (n = 8/group) by gavage (14.8 and 37 mg/kg, one time) or i.p. (7.4 and 37 mg/kg, one time) reduction of acute and chronic inflammation 46 asthmatic rat model (ovalbumin-induced, n = 8/group) oral (4.6 mL/kg) and i.p.…”
Section: Açaímentioning
confidence: 99%
“…The fermented noni fruit exudates and its fraction prevented tumor development, and eradicated up to 75% of existing tumor cells, leading to tumor-free animals for the rest of their lifespan. 44 Another animal study evaluated the effect of a commercial Tahitian Noni ® juice product (percentage content of noni not specified) on tumor development and metastasis in a breast cancer model. This noni juice product was composed of the fruit puree, devoid of the skin and seeds, and standardized in terms of its iridoid content and complemented with grape and blueberry juices.…”
Section: Nonimentioning
confidence: 99%
“…It was found that fNE and its BuOH fraction could prevent and eradicate tumor cells in mice model effectively and prolong the survival of mice receiving tumor cells, which was considered to be mediated by the activation of immune system, especially NK cells. 62,63 Hepatoprotective properties Shibata et al 20 demonstrated that brown rice fermented by Aspergillus oryzae (FBRA) could prevent the development of hepatitis and improve the survival rate of the Long-Evans rat with a cinnamon-like coat color (LEC rats) but showed no effect on the level of copper accumulation in liver tissues, which is different from the findings of other studies regarding the relationship between copper accumulation in liver tissues and hepatitis development. It was claimed that the fermented brown rice may moderate the events following copper accumulation, including the generation of free radicals and/or augmentation of radical scavenging ability.…”
Section: Antitumor Propertiesmentioning
confidence: 95%
“…The antitumor activities of fNE and its two organic fractions, ethyl acetate‐soluble (EtAc) and n‐butanol (BuOH) fraction, were evaluated by intraperitoneal injection or as water supplement for C57BL/6J mice, nude mice or beige mice. It was found that fNE and its BuOH fraction could prevent and eradicate tumor cells in mice model effectively and prolong the survival of mice receiving tumor cells, which was considered to be mediated by the activation of immune system, especially NK cells 62,63 …”
Section: Potential Health Benefitsmentioning
confidence: 99%
“…The medicinal applications that have been investigated include treatment for diabetes, high blood pressure and certain types of cancer, suppression of bacteria and fungi, and accelerated wound healing . The combination of traditional remedies and modern research has led to an expansion in commercial marketing of noni products, especially the fermented fruit juices …”
Section: Introductionmentioning
confidence: 99%